2014
DOI: 10.1161/strokeaha.114.005795
|View full text |Cite|
|
Sign up to set email alerts
|

Transcranial Laser Therapy in Acute Stroke Treatment

Abstract: Background and Purpose-On the basis of phase II trials, we considered that transcranial laser therapy could have neuroprotective effects in patients with acute ischemic stroke. Methods-We studied transcranial laser therapy in a double-blind, sham-controlled randomized clinical trial intended to enroll 1000 patients with acute ischemic stroke treated ≤24 hours after stroke onset and who did not undergo thrombolytic therapy. The primary efficacy measure was the 90-day functional outcome as assessed by the modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 16 publications
2
43
0
15
Order By: Relevance
“…LEDs can also have widely varying total power levels depending on the size of the array and the number and power of the individual diodes (now diodes are available with a power of 3W each). Power densities can also vary quite substantially from the Photothera laser [51] and other class IV lasers [52], which required active cooling or constant movement (~700 mW/cm 2 ), to LEDs in the region of 10–30 mW/cm 2 .…”
Section: Tissue Optics Light Delivery Light Sourcesmentioning
confidence: 99%
“…LEDs can also have widely varying total power levels depending on the size of the array and the number and power of the individual diodes (now diodes are available with a power of 3W each). Power densities can also vary quite substantially from the Photothera laser [51] and other class IV lasers [52], which required active cooling or constant movement (~700 mW/cm 2 ), to LEDs in the region of 10–30 mW/cm 2 .…”
Section: Tissue Optics Light Delivery Light Sourcesmentioning
confidence: 99%
“…Recently, transcranial low‐level light stimulation attracted wide attentions for its amazing therapeutic potential in various psychological and neurological conditions in the nondestructive manner. A serial of controlled clinical trials with a big number of population showed that LLLT was effective in treating neck pain , chronic traumatic injury and ischemic stroke . Some research groups demonstrated the positive therapeutic effect of LLLT on decreasing depression/anxiety and on improving emotional, cognitive, and executive functions for healthy populations .…”
Section: Introductionmentioning
confidence: 99%
“…All together there were three large studies conducted in 1410 stroke patients [NEST-1 (n ¼ 120), NEST-2 (n ¼ 660), NEST-3 (n ¼ 630)] that demonstrated that NIR light delivered transcranially with a class-IV laser is safe, with no significant differences in rates of adverse events with NIR, when compared to sham exposure. [15][16][17] Other preclinical studies and clinical trials have suggested that transcranial photobiomodulation (PBM: laser or light emitting diodes-LED) is safe and effective for acute [18][19][20][21][22] and chronic [23][24][25] traumatic brain injury (TBI) and has beneficial effects on neurodegenerative diseases (Alzheimer's and Parkinson's). 26,27 For the transcranial treatment of major depressive disorder (MDD), both PBM LEDs and lasers have been experimentally tested, although PBM is not FDA-approved for the treatment of MDD.…”
Section: Introductionmentioning
confidence: 99%